An integrated service for Personalised Healthcare and Wellness (PHW). (30th November 2010) - Chen, Su-Shing
At the Systems Biology Lab of the University of Florida, we are developing an integrated system, PHW service, for accessing and storing and monitoring information in personalised medicine. We intend to take a practical approach to build such a system in the framework of clinical and translational sciences of the NIH Roadmap.